Effect of Zeolite Topology and Reactor Configuration on the Direct Conversion of CO2 to Light Olefins and Aromatics - Ramirez, Adrian; Dutta Chowdhury, Abhishek; Dokania, Abhay; Cnudde, Pieter; Caglayan, Mustafa; Yarulina, Irina; Abou-Hamad, Edy; Gevers, Lieven; Ould-Chikh, Samy; De Wispelaere, Kristof; van Speybroeck, Veronique; Gascon, Jorge (ACS catalysis, 2019)
The direct transformation of CO2 into high-value-added hydrocarbons (i.e., olefins and aromatics) has the potential to make a decisive impact in our society. However, despite the efforts of the scientific community, no direct synthetic route exists today to synthesize olefins and aromatics from CO2 with high productivities and low undesired CO selectivity. Herein, we report the combination of a series of catalysts comprising potassium superoxide doped iron oxide and a highly acidic zeolite (ZSM-5 and MOR) that directly convert CO2 to either light olefins (in MOR) or aromatics (in ZSM-5) with high space–time yields (STYC2‑C4= = 11.4 mmol·g–1·h–1; STYAROM = 9.2 mmol·g–1·h–1) at CO selectivities as low as 12.8% and a CO2 conversion of 49.8% (reaction conditions: T = 375 °C, P = 30 bar, H2/CO2 = 3, and 5000 mL·g–1·h–1). Comprehensive solid-state nuclear magnetic resonance characterization of the zeolite component reveals that the key for the low CO selectivity is the formation of surface formate species on the zeolite framework. The remarkable difference in selectivity between the two zeolites is further rationalized by first-principles simulations, which show a difference in reactivity for crucial carbenium ion intermediates in MOR and ZSM-5.